Electrolyte disorders - Bockenhauer, Detlef; Zieg, Jakub (Clinics in perinatology, 2014)
Electrolyte disorders can result in life-threatening complications. The kidneys are tasked with maintaining electrolyte homoeostasis, yet the low glomerular filtration rate of neonatal kidneys, tubular immaturity, and high extrarenal fluid losses contribute to increased occurrence of electrolyte disorders in neonates. Understanding the physiologic basis of renal electrolyte handling is crucial in identifying underlying causes and initiation of proper treatment. This article reviews key aspects of renal physiology, the diagnostic workup of disorders of plasma sodium and potassium, and the appropriate treatment, in addition to inherited disorders associated with neonatal electrolyte disturbances that illuminate the physiology of renal electrolyte handling.
Keywords: nemoci ledvin; Kidney; Electrolyte disorders; novorozenec; Hypernatremia; Glomerular Filtration Rate; lidé; Hypokalemia; Infant, Newborn; Water-Electrolyte Imbalance; vodní a elektrolytová nerovnováha; Hyponatremia; Kidney Diseases; Newborn; ledviny; Hyperkalemia; hodnoty glomerulární filtrace; Renal physiology; Humans